Визначення ємності акумуляторних батарей для систем альтернативного енергозабезпечення споживачів різної потужності - Антипов, Є.О. (Енергетика і автоматика, 2017)
UDC 621.3:620.96 DEFINITION OF CAPACITY OF batteries for alternative energy supply CONSUMER different capacities • I. Antypov Given the wide variety of equipment for renewable energy installations (wind turbines, photovoltaic batteries, solar panels, batteries, etc.), you can develop a lot of energy systems for the combination of different sources. However, the creation of an integrated energy consumers using traditional and/or alternative energy sources requires the inclusion of their accumulation systems or backup power supply, due to certain features of alternative energy sources. That is why there is a need for multiple disparate sources and battery power as part of a system that can provide storage of excess energy generated by the system, and then use it in other periods of time for which the need for it grows. However, a separate interest is the analysis of the feasibility of introducing energy into the batteries of such systems. The purpose of research–determining the capacity of batteries for alternative energy systems of different power consumers. Materials and methods of research. To achieve this goal selected unit of electrical energy of the combined power of consumers, which is based on the use of solar energy and / or electricity network with the possibility of accumulation of excess in the batteries of electric and thermal energy. Detailed description of the components of the system are referred to the source [5]. The use of this system is expected in places where solar energy converters are the main source and the electrical network – subsidiary. Thus, the calculation of the battery, which is determined necessary capacitive power group for the desired duration autonomous power consumers with a minimum temperature of the electrolyte level and charge them, carried out by the method given in [6, 7]. Results of research. Using the proposed method, it was determined the probable duration of continuous power consumers, for example, two 12-volt battery groups, the active power consumers from 500 to 2000 watts and the battery electrolyte temperature: -20 ... + 20 ° C. The nominal capacity of a battery, a member of each group is 100 A·h. In the process of calculating the defined values: possible time continuous power consumers and the coefficient «discharge» battery depending on the load capacity, the number m Bank group of 2 to 4 pieces. As a result, found that for the effective operation of independent power consumers nominal power capacity of 2000 watts for 24 hours and peak (2 hours) capacity of 5000 watts nominal capacity 12-volt battery electric power is located within 315–365 A·h. Conclusions Analyzed the system of complex energy using alternative sources of energy and battery, including: - found that for the effective operation of independent power consumers nominal power capacity of 2000 watts for 24 hours and peak (2 hours) capacity of 5000 watts nominal capacity 12-volt battery electric power is located within 315–365 A·h; - determined the probable duration of continuous power consumers in changing their active power from 500 to 2000 W, which, for example, at 2000 W load capacity and number of batteries in a group of 2 to 4 pcs., is 16, 22 and 31 hours respectively.